Sequential chemotherapy/radiotherapy was comparable with concurrent chemoradiotherapy for stage I/II NK/T-cell lymphoma. (24th October 2017) - Kwong, Y L; Kim, S J; Tse, E; Oh, S Y; Kwak, J Y; Eom, H S; Do, Y R; Mun, Y C; Lee, S R; Shin, H J; Suh, C; Chuang, S S; et al.
Abstract: Background: In stage I/II natural killer (NK)/T-cell lymphoma, concurrent chemoradiotherapy (CCRT) had previously been shown to result in superior outcome compared with anthracycline-containing regimens, which have since been considered ineffective. The role of CCRT in comparison with approaches employing nonanthracycline-containing chemotherapy (CT) and sequential radiotherapy (RT) in such patients remains to be defined. Patients and methods: Three hundred and three untreated patients (207 men, 96 women; median age: 51, 18–86 years) with stage I/II NK/T-cell lymphoma who had received nonanthracycline-containing regimens were collected from an international consortium and retrospectively analyzed. Treatment included single modality (CT and RT), sequential modalities (CT + RT; RT + CT) and concurrent modalities (CCRT; CCRT + CT). The impact of clinicopathologic parameters and types of treatment on complete response (CR) rate, progression-free-survival (PFS) and overall-survival (OS) was evaluated. Results: For CR, stage ( P = 0.027), prognostic index for NK/T-cell lymphoma (PINK) ( P = 0.026) and types of initial treatment ( P = 0.011) were significant prognostic factors on multivariate analysis. On Cox regression analysis, ECOG performance score ( P = 0.021) and PINK-EBV DNA (PINK-E) ( P = 0.002) significantly impacted on PFS; whereas ECOG performance score ( P = 0.008) and stage ( P < 0.001) significantly impacted on OS. For comparing CCRT ± CT and sequential CT + RT, CCRT ± CT patients ( n = 190) were similar to sequential CT + RT patients ( n = 54) in all evaluated clinicopathologic parameters except two significantly superior features (higher proportion of undetectable circulating EBV DNA on diagnosis and lower PINK-E scores). Despite more favorable pre-treatment characteristics, CCRT ± CT patients had CR rate, PFS and OS comparable with sequential CT + RT patients on multivariate and Cox regression analyses. Conclusions: In stage I/II NK/T-cell lymphomas, when effective chemotherapeutic regimens were used, CCRT and sequential CT + RT gave similar outcome.